Mixtures of annual and perennial forage for soybean sucession in crop‑livestock integration systems - Machado, Luís Armando Zago (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the forage production of perennial species and their mixtures with annual species, during the dry season, and the grain yield of soybean grown in succession. Experiments were carried out in 2007 and 2008, in Dourados and São Gabriel do Oeste, MS, Brazil. In 2007, the evaluated treatments were Urochloa brizantha ('Xaraés') and Megathyrsus maximus ('Tanzania'), single or in mixtures with Eleusine coracana (finger millet), Pennisetum glaucum (pearl millet) and Sorghum bicolor (forage sorghum). In 2008, U. decumbens and the cultivars Tanzania and Xaraés, single or in mixtures with pearl millet and forage sorghum, were evaluated. The evaluations were done in forages under successive cuts, during the dry season, and in soybean grown in succession, in the summer. Mixtures of annual and perennial species do not increase forage production, but improve its distribution throughout the dry season. The annual forages have higher participation in the forage production of mixtures at the beginning of the dry season, and the perennials at the end of that season. Leaf/stem ratio of individual perennial forages is greater than that of the mixtures. The evaluated treatments have no effect on soybean grown in succession.